Teachers' Strategies in Using Block Play to Manage Children who Refuse to be Left by Their Parents at Aisyiyah 39 Kratonan Kindergarten - Yuli Astutik; Sri Slamet (Universitas Muhammadiyah Surakarta, 2025)
This study aims to explore teachers' strategies in using block play as a means to address young children who experience difficulty separating from their parents at TK Aisyiyah 39 Kratonan, Surakarta. The phenomenon of separation anxiety often becomes an obstacle in the learning process, independence, and socialization of early childhood. To gain a deeper understanding of this phenomenon, the study employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The study involved 7 children, aged 5-6 years who showed moderate to high separation anxiety, selected through purposive sampling, ensuring that the research subjects matched the focus of the intervention. The findings reveal that the implementation of block play effectively diverts children's attention from emotional dependence on their parents toward enjoyable and meaningful learning activities. Through block play activities, children began to show improvements in independence, courage to be left by their parents, adaptability in the school environment, and social interaction with peers. Supporting factors for the success of this strategy include the availability of adequate block play materials, the warm and communicative role of teachers, and active parental involvement in the child's adaptation process. However, several challenges were identified, such as limited play equipment, short learning time, and uneven teacher skills in managing play-based activities. The implications of this study emphasize that block play functions not only as a play medium but also as an effective psychological, social, and pedagogical intervention tool to support early childhood development.